Modal Sosial Komunitas Wilayah Pesisir Dalam Mengelola Mangrove di Kabupaten Jember - Nur Anggraeni, Esti Mega; Subekti, Sri (Fakultas Pertanian, Universitas Lampung, 2022)
The research aimed to identify elements of social capital, typology and function of social capital of Pokmaswas in managing mangroves. The research location was determined purposively, namely the Pokmaswas Bahari Lestari in Mayangan Village, Gumukmas District, Jember Regency. The research used descriptive qualitative method and the informants were determined purposively. The data collected by using the methods of observation, interviews, and document study then were analyzed using the analysis of the Milles and Huberman models. The results showed that: 1) the elements of social capital consisted of five elements, namely networks, norms, trust, reciprocity and cooperation. The most dominant elements were trust, reciprocity and cooperation. 2) There were three types of social capital, namely: bonding, bridging, and linking. Bonding was in the form of norms, empathy, tolerance, and trust, while bridging was in the form of field fishery instructors playing a role in assisting Pokmaswas in obtaining assistance and information from outside. Meanwhile, linking was in the form of external parties playing a role in helping mangrove management, including the Jember Regency and Provincial Fisheries Service. The function of social capital was to strengthen the groups to achieve common goals in mangrove management.